2,4,6,-trihydroxy-3-geranylacetophenone (tHGA) suppresses chronic allergic airway inflammation in ovalbumin-sensitized mice via intraperitoneal route - Ismail, Norazren; Jambari, Nuzul Noorahya; Tham, Chau Ling; Harith, Hanis Hazeera; Shaari, Khozirah; Israf Ali, Daud Ahmad (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Asthma is a condition characterized by eosinophilic airway inflammation and remodelling that involves several pathological changes, including subepithelial fibrosis, mucus hypersecretion, smooth muscle growth, and vascular changes. The present study aimed to determine the effect of tHGA administered intraperitoneally in a chronic asthma mouse model that closely mimics the human asthma. Methods: Ovalbumin-sensitized and challenged BALB/c mice were i.p. administered with tHGA at different doses (20 and 2 mg/kg). Respiratory function was measured, and brochoalveolar lavage, blood and lung samples were then obtained and analyzed. Results: The airways of OVA-induced mice developed increased pulmonary inflammation with increased levels of cytokines, chemokines, and changes in vascular permeability. Intraperitoneal administration of tHGA in OVA-induced mice significantly and dose-dependently inhibited the airway inflammation, production of immunoglobulin E, Th2-type cytokines and chemokines, and inflammatory mediators. Treatment with tHGA also significantly reduced the airway hyperresposiveness in response to increased methacholine doses. Conclusion: This study demonstrates that the efficacy of tHGA in alleviating chronic asthmatic symptoms in mouse model improved significantly when administered intraperitoneally compared to oral route. Furthermore, this study also supports that tHGA has a therapeutic potential in chronic asthma management by acting as a cysteinyl leukotrienes (CysLT) inhibitor.